Pengalaman Lingkungan Lingkungan Sebagai Pendekatan Pengembangan Pariwisata Daerah - Raksadjaya, Rini (Journal of Regional and City Planning, 2001)
This paper discusses the relationship between tourism and tourist’s impression on its environment. It argues that tourists are willing to have and observe a comprehensive tourism activities in which more Contact & understanding on local people and possible participation in their daily lives is preferable than merely visit and see the tourist object. Decision makers could consider this approach in developing any local tourism activities.